Acute Corticotropin-Releasing Factor Receptor Type 2 Agonism Results in Sustained Symptom Improvement in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome - Pereira, Gerard; Gillies, Hunter; Chanda, Sanjay; Corbett, Michael; Vernon, Suzanne D.; Milani, Tina; Bateman, Lucinda (Frontiers in Systems Neuroscience, 2021)
Background: myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a complex multi-symptom disease with widespread evidence of disrupted systems. The authors hypothesize that it is caused by the upregulation of the corticotropin-releasing factor receptor type 2 (CRFR2) in the raphé nuclei and limbic system, so impairing the ability to maintain homeostasis. The authors propose utilizing agonist-mediated receptor endocytosis to downregulate CRFR2. Materials and Methods: this open-label trial tested the safety, tolerability and efficacy of an acute dose of CT38s (a short-lived, CRFR2-selective agonist, with no known off-target activity) in 14 ME/CFS patients. CT38s was subcutaneously-infused at 1 of 4 dose-levels (i.e., infusion rates of 0.01, 0.03, 0.06, 0.20 μg/kg/hour), for a maximum of 10.5 hours. Effect was measured as the pre-/post-treatment change in the mean 28-day total daily symptom score (TDSS), which aggregated 13 individual patient-reported symptoms. Results: ME/CFS patients were more sensitive to the transient hemodynamic effects of CRFR2 stimulation than healthy subjects in a prior trial, supporting the hypothesized CRFR2 upregulation. Adverse events were generally mild, resolved without intervention, and difficult to distinguish from ME/CFS symptoms, supporting a CRFR2 role in the disease. The acute dose of CT38s was associated with sustained improvement (at least 28 days after treatment) in mean TDSS that correlated both with total exposure and pre-treatment symptom severity. At an infusion rate of 0.03 μg/kg/hour, mean TDSS improved by -7.5±1.9 (or -25.7%, p=0.009), with all monitored symptoms improving. Conclusion: the trial supports the hypothesis that CRFR2 is upregulated in ME/CFS, and that acute CRFR2 agonism may be a viable treatment approach warranting further study. Clinical Trial Registration: ClinicalTrials.gov identifier: NCT03613129.